Multifunction Transceiver for Data Communication, Radar Sensing and Power Transfer - Thomas Micallef; Intikhab Hussain; Ke Wu (Electromagnetic Science)
The future of wireless systems is anticipated to revolutionize human connectivity through a diverse range of applications. The integration of multiple wireless functionalities into a unified system presents a critical challenge due to conflicting requirements in transceiver architecture and signal processing. Recent investigations are directing attention towards the development of systems that serve dual functions, like simultaneous wireless information and power transfer and radar-communication, aimed at boosting operational efficiency and ensuring seamless communication among different wireless capabilities. This review paper aims to discuss the architectural aspects of the integration of radar sensing, data communication, and power transfer. Firstly, the integration of radar sensing and data communication is studied for both cooperating and non-cooperating radar systems with conventional and interferometric architectures. Secondly, the power harvesting approach and internal energy recycling are discussed for the fusion of data communication and energy harvesting. Thirdly, radar sensing and power transfer integration is considered with special focus on harmonic backscattering and self-powered radars. Lastly, a roadmap for next-generation multifunction systems is outlined by considering several scenarios of multiplexing and architectures.